Correction: Engineering microbial physiology with synthetic polymers: cationic polymers induce biofilm formation in Vibrio cholerae and downregulate the expression of virulence genes. Issue 39 (27th September 2018) - Perez-Soto, Nicolas; Moule, Lauren; Crisan, Daniel N.; Insua, Ignacio; Taylor-Smith, Leanne M.; Voelz, Kerstin; Fernandez-Trillo, Francisco; Krachler, Anne Marie
Abstract : Correction for 'Engineering microbial physiology with synthetic polymers: cationic polymers induce biofilm formation in Vibrio cholerae and downregulate the expression of virulence genes' by Nicolas Perez-Soto et al., Chem. Sci., 2017, 8, 5291–5298.